Formulation and Antibacterial Activity Test Liquid Soap with Eugenol Variant from Clove Leaf Oil (Eugenia aromaticum) Against Bacteria Staphylococcus aureus - Estikomah, Solikah Ana; Azzahra , Adhinda Eugenia; Yulisa; Anugrah, Anugrah (BIOEDUSCIENCE, 2025)
Background: The skin, as the largest organ of the body, hosts various types of bacteria. Excessive sebum production combined with bacterial infections can lead to skin issues such as irritation. Although chemical-based antiseptic soaps are effective, they may negatively impact both the environment and skin health. This has increased public interest in natural alternatives, such as cloves (Eugenia aromaticum), which contain eugenol an active compound with antiseptic, anti-inflammatory, and antibacterial properties. This study aimed to formulate a clove leaf oil-based liquid soap with varying concentrations of clove leaf oil: F1 (0%), F2 (4%), F3 (6%), and F4 (8%), and to evaluate its physical properties and antibacterial activity against Staphylococcus aureus. Methods: The disc diffusion method was employed to assess antibacterial activity. Results: The organoleptic test showed that the soap had a distinctive clove aroma, yellow color, and a liquid to thick homogeneous consistency. The pH values ranged from 8.97 to 9.14, foam stability ranged between 84.37% and 88.18%, viscosity ranged from 2510.72 to 6190.57 cP, and spreadability varied from 3.39 to 6.42 cm. Antibacterial testing revealed inhibition zones of 2.87 mm (F1), 7 mm (F2), 10 mm (F3), and 15.25 mm (F4), indicating increasing antibacterial activity with higher clove oil concentrations. Conclusions: The F2 formula was identified as the most balanced, with acceptable pH, optimal foam stability, moderate viscosity, and a 7 mm inhibition zone classified in the medium category. This study highlights the potential of clove leaf oil as a natural antibacterial agent in liquid soap formulations.